EVALUATION OF MODIFIED NITRITE TEST AS A DIAGNOSTIC TEST IN URINARY TRACT INFECTION OF CHILDREN - JAIN, PUNEET; MALVIA, SUNNY; KHAN, NIHA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Urinary tract infection (UTI) is common infection in children. Urine culture is the gold standard method for diagnosing urine infection but it takes more than 48 h to give results. The objective is to evaluate the diagnostic ability of modified nitrite test as a rapid diagnostic screening test for diagnosis of UTI in children. Methods: An observational and cross-sectional study was conducted in a tertiary care hospital in Udaipur over a period of 1 year. Children aged up to 60 months with suspected UTI were enrolled in the study. Children with congenital urogenital anomalies and prior antibiotic treatment were excluded from the study. Urine culture and modified nitrite test was done for every children. Results: Ninety children with suspected UTI were enrolled in the study. Urine culture was positive in 14 (15.55%) out of 90 urine samples. When modified nitrite test was compared to positive urine culture, true positives were 9 and 1 was false positive. Sensitivity, Specificity, PPV, NPV, and Accuracy was 64.29%, 98.68%, 90%, 93.75%, and 93.33%, respectively. Conclusion: Sensitivity and specificity of modified nitrite test are good enough as a diagnostic test for detection of UTI. It can be used as a point of care test for rapid screening and identifying the cases.